Evaluation of extraction procedures for 2‐DE analysis of aphid proteins. Issue 3 (14th January 2013) - Yiou, Pan; Shaoli, An; Kebin, Li; Tao, Wang; Kui, Fang; Hua, Zhang; Yu, Sun; Xun, Yang; Jinghui, Xi
<x xml:space="preserve">Abstract</x> Protein sample preparation is a crucial step in a 2‐DE proteomics approach. In order to establish a routine protocol for the application of proteomics analysis to aphids, this study focuses on the specific protein extraction problems in insect tissues and evaluates four methods to bypass them. The approaches of phenol extraction methanol/ammonium acetate precipitation (PA), TCA/acetone precipitation, PEG precipitation, and no precipitation were evaluated for proteins isolation and purification from apterous adult aphids, Sitobion avenae. For 2‐DE, the PA protocol was optimal, resulting in good IEF and clear spots. PA method yielded the greatest amount of protein and displayed most protein spots in 2‐DE gels, as compared with the TCA/acetone precipitation, PEG precipitation and no precipitation protocols. Analysis of protein yield, image quality and spot numbers demonstrate that the TCA/acetone precipitation protocol is a reproducible and reliable method for extracting proteins from aphids. The PEG precipitation approach is a newly developed protein extraction protocol for aphids, from which more unique protein spots can be detected, especially for detection of acid proteins. These protocols are expected to be applicable to other insects or could be of interest to laboratories involved in insect proteomics, despite the amounts and types of interfering compounds vary considerably in different insects.